Improving Human Resources in the Social Affairs Office Through Work Stress Management Psychoeducation Programs - Agustin Atmaningrum; Siti Nur'ainun Zakiyah; Nuratthahirah Ansar (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Work stress is a critical issue in organizations because it impacts employee psychological health and performance. Initial findings among employees of the South Sulawesi Provincial Social Service indicate moderate stress levels, necessitating psychoeducational intervention. This community service activity aims to improve stress management knowledge through interactive lectures, brainstorming, and discussions. Evaluation using a pre-post test analyzed with Shapiro-Wilk and paired samples t-test on 20 participants showed a significant increase (t(19) = -6.124, p < .001) with a large effect size (Cohen's d = 1.369). These results confirm that psychoeducation is effective in improving participants' understanding of work stress and coping strategies. This program is recommended for ongoing implementation as part of employee capacity building efforts.